(3CSGSjGJ GdEOGQI GdeGdjI (B:s (3GdJMdjd GdeGdj ddeTQhYGJ GdLOjOI (B/s - (3GdMfGhj, eMeO UGdMs; (3fgGd, aQjO eUWais ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2003)
(3EWdGdI YGeI Ydi GdEOGQI GdeGdjI,Jbjje GdGfaGb GdQCSeGdj aj Xd XQha GdJCcO GdcGed,bQGQGJ GdGfaGb GdQCSeGdj aj Xd XQha GdNWQ(B1(3,bQGQGJ GdGfaGb GdQCSeGdj aj Xd XQha GdNWQ(B2(3,JcdaI GdCehGd,GJNGP bQGQ GdGSJKeGQ aj GdeTQhY ef hLgI fXQ bhejI,GJNGP bQGQ GdGSJKeGQ aj GdeTQhY ef hLgI fXQ ESdGejI,JCKQ gjcd QCS GdeGd Ydi bjeI GdefTCI,JCKQ SjGSI GdJhRjYGJ Ydi bjeI GdefTCIs
(3HHdjhZQGajG(B:(3U(B.426s
Keywords: (3GdGOGQI GdeGdjIs; (3GdGSJKeGQs; (3GdSjGSI GdeGdjIs